Analisis Pengaruh Variabel Makro Ekonomi Terhadap Return Saham Pada Bank Bumn di Bursa Efek Indonesia - Herman, Bayu Mirama; Azansyah, Azansyah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This study aims to analyze the influence of macroeconomic variables, namely BI Rate, Rupiah Exchange Rate, Inflation, and Economic Growth, on Stock Returns of State-Owned Banks listed on the Indonesia Stock Exchange. The problem to be solved is the uncertainty regarding the significant influence of these variables on stock returns, which in previous studies have produced mixed results. By understanding this relationship, it is expected to provide better insight for investors and policy makers in making investment decisions and designing economic policies. The research method used is a quantitative approach with multiple linear regression analysis, where the analysis methods include descriptive statistical analysis techniques, classical assumption tests, multiple linear analysis tests, and hypothesis tests. The results of the analysis show that simultaneously, all independent variables have a significant effect on Stock Returns, which can be proven with a probability level (F-statistic) of 0.000000, < 0.05 Probability level (F-statistic). However, partially, only Rupiah Exchange Rate, Inflation, and Economic Growth showed a significant influence, this can be proven by Rupiah Exchange Rate with a t-count value of 4.983 > 2.004 t table, then for inflation it is proven by a t-count value of 6.664 > 2.004 t-table and for economic growth it is proven by a t-count value of 2.546 > 2.004 t-table, while BI Rate has no effect, this is proven by BI Rate with a t-count value of 0.865 < 2.004 t-table. The implication of this study is the importance of considering macroeconomic factors in making investment decisions, as well as providing recommendations for further research to include micro factors and expand the scope of research objects. The contribution of this study is expected to enrich the literature on the influence of macroeconomic variables on the stock market, especially in the context of state-owned banks in Indonesia.